2020
DOI: 10.1177/0963689720978722
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes of Mesio Temporal Lobe Epilepsy and Prognostic Biomarkers of Brain Low-grade Gliomas Based on Bioinformatics Analysis

Abstract: Mesio temporal lobe epilepsy (MTLE) syndrome is the most common form of intractable epilepsies. Meanwhile, seizures are common in patients with cancer as a consequence of brain tumors, including brain low-grade gliomas (LGG). However, the underlying molecular mechanisms of MTLE remain poorly understood. Also, the relationship between MTLE and LGG needs our attention. In this study, we aimed to investigate the hub genes and potential mechanism in MTLE, and the relationship between MTLE and LGG, the gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…We also identified the KEGG pathway neuroactive ligand-receptor interaction, consisting of DEGs encoding neuroreceptors, such as GRIA4 , which is significantly associated with a molecular mechanism involved in temporal epilepsy [ 63 ]. Indeed, a mutation in the GRIA4 gene, which encodes an AMPA receptor (AMPA-R) subunit expressed in cortical as well as thalamic neurons, leads to the absence of seizures [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also identified the KEGG pathway neuroactive ligand-receptor interaction, consisting of DEGs encoding neuroreceptors, such as GRIA4 , which is significantly associated with a molecular mechanism involved in temporal epilepsy [ 63 ]. Indeed, a mutation in the GRIA4 gene, which encodes an AMPA receptor (AMPA-R) subunit expressed in cortical as well as thalamic neurons, leads to the absence of seizures [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has indicated that Jun had the potential to serve as a prognostic marker for neuropathic pain ( Yang et al, 2018 ). JUN was identified as a potential biomarker for the prognosis of brain low-grade gliomas ( Xu et al, 2020 ). Besides, the c-JUN-medicated signaling pathway was an important BP involved in the pathogenesis of hippocampal neuronal damage in kainite-induced epilepsy ( Lee et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…As we know, it is difficult to collect hippocampal tissue from children with VPA-resistant epilepsy in clinical practice. In order to efficiently find the miRNA that regulates HIF-1α in VPA-resistant epilepsy, this study firstly performed integrated bioinformatics analysis on the hippocampal tissue of patients with drug-resistant epilepsy in public databases referring to the previous method ( Xu et al, 2020 ). Subsequently, the miRNAs that potentially regulate the expression of HIF-1α were selected.…”
Section: Discussionmentioning
confidence: 99%